Do we need a radical redefinition of secularism?: A critique of Charles Taylor - Akan, Murat (Politics and religion, 2024)
Charles Taylor's "radical redefinition of secularism" has a significant place in the post-9/11 research on secularism. He replaces secularism's "old" paradigm, separation between state and religious institutions, with a "new" one, responding to diversity. Taylor appeals to French laïcité in-itself as the old paradigm. With an analysis of the parliamentary debates at the institutional origins of the old paradigm in the Third French Republic, this article questions whether Taylor's redefinition of secularism is truly radical. This historical intervention in Taylor's "radical redefinition" reformulates his novelty as the reconfiguration of the relation between generality of laws and meaning worlds in the institutional response to diversity. The Third Republic pushed generality in laws against diverse meaning worlds. Taylor (with Jocelyn Maclure) demands that general laws reasonably accommodate "meaning-giving convictions." I explore this reversal and argue that it's questionable Taylor offers a radical redefinition of secularism - or even that we need one.